Treating Postlaparoscopic Surgery Shoulder Pain with Acupuncture. (23rd April 2014) - Kreindler, Gur; Attias, Samuel; Kreindler, Anna; Hen, Haim; Haj, Bassel; Matter, Ibrahim; Ben-Arye, Eran; Schiff, Elad
Abstract : Objective. The purpose of this study was to examine the effect of acupuncture on postlaparoscopic shoulder pain (PLSP) which is a common side effect in patients undergoing abdominal laparoscopic surgery. Methods. Patients with moderate to severe PLSP in spite of analgesic treatment, which were referred by the medical staff to the Complementary-Integrative Surgery Service (CISS) at our institution, were provided with acupuncture treatment. The severity of PLSP and of general pain was assessed using a Visual Analogue Scale (VAS) from 0 to 10. Pain assessment was conducted prior to and two hours following acupuncture treatment. Acupuncture treatment was individualized based on traditional Chinese medicine diagnosis. Results. A total of 25 patients were evaluated during a 14-month period, from March 2011 to May 2012. A significant reduction in PLSP (mean reduction of 6.4 ± 2.3 P < 0.0001 ) and general pain (mean reduction 6.4 ± 2.1 P < 0.0001 ) were observed, and no significant side effects were reported. Conclusion. Individualized acupuncture treatments according to traditional Chinese medicine principles may improve postlaparoscopic shoulder pain and general pain when used in conjunction with conventional therapy. The primary findings of this study warrant verification in controlled studies.